2021
DOI: 10.1093/eurpub/ckab164.060
|View full text |Cite
|
Sign up to set email alerts
|

How are countries supporting health workers? Data from the COVID-19 Health System Response Monitor

Abstract: Background Health workers have been at the forefront of treating and caring for patients with COVID-19. They were often under immense pressure to care for severely ill patients with a new disease, under strict hygiene conditions and with lockdown measures creating practical barriers to working. This study aims to explore the range of mental health, financial and other practical support measures that 36 countries in Europe and Canada have put in place to support health workers and enable them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 0 publications
1
40
0
Order By: Relevance
“…Some countries have rolled out national hazard pay policies for frontline nurses and other healthcare professionals, such as in Poland. Nurses in Poland were provided with monthly cash benefits to compensate them for their absence from work after getting in contact with COVID-19 patients, while financial bonuses were offered to medical staff who had rendered their service amidst COVID-19 in other countries (Williams et al, 2020). One study performed in Ethiopia reported that equitable salary is essential in maintaining the satisfaction of nurses (Ayalew et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some countries have rolled out national hazard pay policies for frontline nurses and other healthcare professionals, such as in Poland. Nurses in Poland were provided with monthly cash benefits to compensate them for their absence from work after getting in contact with COVID-19 patients, while financial bonuses were offered to medical staff who had rendered their service amidst COVID-19 in other countries (Williams et al, 2020). One study performed in Ethiopia reported that equitable salary is essential in maintaining the satisfaction of nurses (Ayalew et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Countries such as Romania, Malta, and Poland implemented free accommodation for healthcare professionals once they were isolated from their families amidst the COVID-19 pandemic. In some parts of the UK, healthcare professionals were given free access to transportation, while in Finland, they were given free-of-charge parking near healthcare facilities (Williams et al, 2020). The alleviation of the burden of the nurses through the implementation of the protocols mentioned above in different countries may have greatly contributed to maintaining the ProQol of nurses.…”
Section: Discussionmentioning
confidence: 99%
“…These were intended to support health workers and enable them to do their job. These included additional nancial support and compensation above normal salaries to health care workers involved in the COVID-19 response, a lump sum payment to families in the event of death of a health worker following COVID-19 infection, allowances to cover childcare costs during the crisis in the case where a health worker's partner could not take paid leave, and temporary salary increment (27). It is reported that in Sierra Leon during the Ebola epidemic risk allowance motivated health workers (83).…”
Section: Discussionmentioning
confidence: 99%
“…This has added more burden and responsibility to the HCWs. In some countries nevertheless, childcare facilities are provided for HCWs, with some paid allowances for childcare costs where the HCW’s partner could not take paid leave, and some hospitals independently organised childcare for the workers (Williams, et al , 2020). US Centres for Disease Control and Prevention (CDC) guideline says that childcare for HCWs should be prioritised.…”
Section: Social Protection – the Meaning And Contextmentioning
confidence: 99%
“…Along the line, social protection "has been used in disaster response, as a bridge between humanitarian assistance and development processes" (European Commission, 2019, p. 4) when it helps to address the economic and social disruptions that threaten the well-being of individuals, families, communities and societies (Drolet, 2020). There is a range of measures of social protection implemented by countries, from mental health support, financial bonuses and practical supports such as free accommodation and transport (Williams et al, 2020). Social protection as a human right is enshrined in the Universal Declaration of Human Rights 1948.…”
Section: Introductionmentioning
confidence: 99%